Moisture Transfer Finite Element Modeling with Soil-Water Characteristic Curve-Based Parameters and its Application to Nhan Co Red Mud Basin Slope - Hoang, Nguyen Van; Viet Hung, Hoang; Van Dung, Pham (VNU Journal of Science: Earth and Environmental Sciences, 2021)
Since the year of 2017, landslides at the red mud basins in Nhan Co alumina factory, Dak Nong province have been occurring during the rainy season. The change of the soil physical and mechanical parameters due to rainwater infiltration has been considered as the main factor of the slope instability. The soil cohesion and angle of internal friction depend greatly on the soil moisture. Specifically, soil with a lower moisture content has a higher shearing strength than that in soil with higher moisture content. The finite element modeling of moisture transfers in unsaturated soils through the relationship between soil moisture, soil suction, unsaturated permeability and soil-moisture dispersivity is capable of accurately predicting the wetting front development. The element sizes and time steps have been selected based on detailed analysis of analytical error estimation and on the numerical simulations with different element sizes numerical simulation errors. Soil samples had been taken then the soil different suctions and corresponding soil moisture values have been determined in the laboratory. The soil water characteristic curve (SWCC) parameters ( a , n and m ) have been determined by the best fitting using the least squared error method. The hydraulic conductivity of the saturated soil, one of the key input parameters was also determined. The results of the application to the study area's slope has shown that the wetting front depth could be up to 8 meters for 90 days of moisture transfer due to the rainwater infiltration. The wetting front depth and the length of the intermediate part of the moisture distribution curve have increased with the infiltration time. The soil moisture distribution with a depth is an essential information to have soil strength parameters for the slope stability analyses. The slope stability analysis with the soil shear strength parameters which are strictly corresponding with the moisture change would provide the most accurate and reliable slope stability results and provide more reliable slope stabilization solutions.